The Implications of Bringing Freshman Composition to a British University - Baratta, Alex (Journal of Academic Writing, 2012)
This paper discusses the results of a reflective case study involving academic writing within an undergraduate programme at a British university. Specifically, the study focuses on the positioning of the students’ central claims within their essays – and subsequent essay structure – and how this differs from a specific structure often taught within the US Freshman Composition class. Coming from this teaching background in the US, I made the assumption that such pedagogy would be transferable when I began teaching academic writing in a UK university in 2003; however, from my experience students have tended to resist placing their central claims within the introduction and this study might therefore illustrate a potential pedagogic issue that US trained writing professionals could face if teaching academic writing in Britain. The analysis of 535 essays from all three years of the programme, in addition to questionnaires completed by staff, students, and members of the European Association for the Teaching of Academic Writing (EATAW), help to shed light on the nature of the thesis statement in the British academic writing context.